Case Report: Rituximab Improved Epileptic Spasms and EEG Abnormalities in an Infant With West Syndrome and Anti-NMDAR Encephalitis Associated With APECED - Kawano, Go; Yokochi, Takaoki; Nishikomori, Ryuta; Watanabe, Yoriko; Ohbu, Keizo; Takahashi, Yukitoshi; Shintaku, Haruo; Matsuishi, Toyojiro (Frontiers in Neurology, 2021)
Background: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy is a rare autosomal recessive disorder caused by a mutation in the autoimmune regulator gene. Patients with autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy typically exhibit hypoparathyroidism, adrenocortical failure, and chronic mucocutaneous candidiasis. There are only a few case reports of autoimmune encephalitis during autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy, but not as an initial manifestation. Furthermore, there are no reports of patients with infantile spasms/West syndrome with autoimmune encephalitis, partly because the median age for paediatric patients with anti-N-methyl-D-aspartate receptor encephalitis, which is the most frequent and best characterised in paediatric autoimmune encephalitides, is 13–14 years. Herein, we present a case of a 3-month-old infant with autoimmune encephalitis as an initial manifestation of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy who later developed infantile spasms/West syndrome. Case Presentation: A 3-month-old girl was admitted to our hospital with a fever, involuntary movements in all four limbs, and right-side facial palsy. Acute central nervous system demyelination diseases were suspected from neuroimaging findings and the presence of the cerebrospinal fluid oligoclonal band. She did not respond to multiple methylprednisolone pulse therapies and later developed infantile spasms/West syndrome and diabetes mellitus. Rituximab, a chimeric mouse/human monoclonal antibody directed against human CD20 which depletes B cells, was initially administered as a treatment for autoimmune encephalitis. Unexpectedly, this treatment resulted in complete spasm cessation and resolution of hypsarrhythmia. The patient eventually showed severely delayed developmental milestones, and her electroencephalography findings showed periodic generalised slow spike-and-wave pattern. Conclusions: Despite the limited ability to extrapolate findings from a single case, rituximab's effects may suggest that B cells play a crucial role in infantile spasms/West syndrome mechanisms; use of rituximab as an aetiology-specific treatment for infantile spasms/West syndrome patients with autoimmune encephalitis or its effectiveness for infantile spasms/West syndrome patients with other underlying mechanisms warrants further investigation.